Implementasi Undang-undang Nomor 38 Tahun 1999 tentang Pengelolaan Zakat - Nur Jihad (Jurnal Hukum IUS QUIA IUSTUM, 2001)
The rapid ofindustrious and economical development as a enterpreunership need thesolution of calculation and charge of tax obligation in orderthat the ommision of povertycaused byeconomical recession cab be improved. Itremembers thatthe managementoftithe (zakat) in theoldIslamicJurisprudence isstill limited, while thelevel ofcomplexitybecause of economical development is very multl demensiona. This article is going tosee deeplyhow Is implementation of regulation number 38 year of 1999 about tithe(zakat) management operationally. Is itsignificant asndeffective enough or it faces thehandicaps and other problem in which it needs solution.